International Intervention to Protect Human Rights and Minorities between the Provisions of the Responsibility to Protect and Respect for States Sovereignty - Haouari, Hamza (Journal of Legal Studies and Researches, 2023)
Our study examines the extent to which the responsibility to protect mechanism reconciles between intervention to protect human rights and the sovereignty of states, and concluded that there is no other mechanism to date that guarantees reconciliation as much as the responsibility to protect guarantees it, with the need to define its frameworks more precisely and establish legal controls for them.